Acupuncture Treatment for Cough-Variant Asthma: A Meta-Analysis. (2nd April 2021) - Xiong, Jian; Qi, WenChuan; Yang, Han; Zou, SiTing; Kong, Jing; Wang, ChengLong; Zhou, YuanFang; Liang, FanRong
Abstract : Background . In recent years, there have been many clinical reports on acupuncture treatment of cough-variant asthma, but no researcher has objectively analysed and evaluated the efficacy and safety of acupuncture treatment of cough-variant asthma from the perspective of evidence-based medicine. Objective . To systematically evaluate the clinical efficacy and safety of acupuncture in treating cough-variant asthma and to provide reference values for clinical decision-making. Methods . The comprehensive computer retrieval Chinese journal full-text database (CNKI), Chinese science and technology periodical database (VIP), ten thousand data knowledge service platform (WanFang Data), PubMed, Embase, and the Cochrane Library were used to collect literature for relevant randomized controlled trials (RCT) of acupuncture treatment of cough-variant asthma, as well as to retrieve papers and add reference retrieval after literature review, in accordance with the standard of literature filtering, data extraction, and quality evaluation. The data were meta-analysed using ReviewManager5.3 software recommended by Cochrane. Results . A total of 11 randomized controlled clinical studies were screened and included, comprising 929 patients. The results of the meta-analysis showed that, compared with the control group, acupuncture intervention on CVA could enhance the total clinical effectiveness rate, reduce the relapse rate of drug withdrawal, relieve symptoms of cough, phlegm, and diaphragmatic congestion, and improve lung function-related indicators and immune inflammation indicators. There were statistically significant differences in all efficacy evaluation criteria. Conclusion . The clinical curative effect of acupuncture treatment for cough-variant asthma is precise and has certain advantages in relieving symptoms and reducing the recurrence rate. However, the low quality of the evaluation in the RCT research literature is a problem, and more high-quality clinical randomized controlled trials are needed to further verify the comprehensive clinical efficacy and safety of this treatment. Registration number: PROSPERO (no. CRD42020155244) (https://www.crd.york.ac.uk/prospero/ ).